Catalytic Asymmetric Hydrogenation of Dehydroamino Acid Esters with Biscarbamate Protection and Its Application to the Synthesis of xCT Inhibitors. Issue 20 (8th March 2019) - Yasuno, Yoko; Mizutani, Iho; Sueuchi, Yuki; Wakabayashi, Yuuka; Yasuo, Nozomi; Shimamoto, Keiko; Shinada, Tetsuro
Abstract: Catalytic asymmetric hydrogenation of dehydroamino acid esters with biscarbamate protection was examined for the first time to prepare optically active amino acids. The new method was successfully applied to the synthesis of new cystine–glutamate exchanger inhibitors. Abstract : Orthogonal protection : Dehydroamino acid esters with biscarbamate protection were employed for the catalytic asymmetric hydrogenation for the first time to give optically active amino acid esters. The new method was successfully applied to the development of cystine–glutamate exchanger (xCT) inhibitors (see scheme).